Winning Over the Players: Investigating the Motivations to Play and Acceptance of Serious Games - Jacobs, Ruud S. (2021)
Serious games are designed to educate, train, or persuade their players on specific topics and issues. While a lot of studies have sought to prove the effects of these games, the overall image and legitimization of serious games has not benefited fully from these efforts. Indicating that the issue stems from the difference between the captive audience exposed to games in effects studies and the contexts in which people come to play serious games in everyday life, the current article sketches out the research that needs to be performed before this gap can be filled. Three theoretical perspectives are offered, in turn looking at serious games as forms of (promotional) communication, personal media experiences, and technological innovations. This analysis results in insights relating to (among others), how the identity of serious games might hinder their diffusion, how expected gratifications could fail to match the intentions of these games, and what could cause someone to ‘adopt’ a serious game. Based on the insights gained by applying these lenses, potential factors are listed and linked to methodologies that could prove or disprove their importance. These methodologies involve quantitative and qualitative investigations to create a deeper picture of how potential players approach serious games. The article concludes with open questions to investigators and industry professionals generated from this process.